DC/DC charging controller design - Tan, Yong Ann. (2012)
This report presents a design and simulation of DC/DC bi-directional charging controller. This system is used to control the flow of power between bus (DC link) and the battery bank. It is designed to work in three different modes of operation assigned by users.